Pengaruh Tranformational Leadership, Work Environment Terhadap Employee Performance Dengan Islamic Motivation Sebagai Variabel Intervening (Studi Pada Bank Jatim Syariah Cabang Jember) - Nursaidah Nursaidah; Tatit Diansari Reskiputri (Universitas Muhammadiyah Jember, 2021)
AbstractEmployees have a big and important role in the success of an organization. Benchmarks for organizational success can be seen from employee performance. Employee performance means employee productivity and output as a result of employee development and ultimately will affect organizational effectiveness. Good performance can be achieved through good transformational leadership, through motivation based on the Islamic values of employees. Much research has been conducted examining the relationship between motivation and performance. However, some things have not shown success and there are research gaps. The results of the study have a major effect on employee performance appraisal Bank Jatim Syariah Jember Branch tries to measure employee performance from transformational leadership and work environment through the motivation of each employee. This decision-making is based on existing theories. The role of motivation is expected to be able to make the employees of Bank Jatim Syariah Branch of Jember will be better than other areas that have achieved their goals. Keywords: Transformational Leadership, Work Environment, Islamic Motivation, and Employee Performance